Home dialysis in french speaking countries in 2020 (RDPLF database) - Christian Verger; Ghislaine Veniez; Marie-Christine Padernoz; Emmanuel Fabre (RDPLF, 2021)
The RDPLF collects the main peritoneal dialysis data from centers in French-speaking countires and, since 2012, home hemodialysis (HHD) data. This article presents a summary of the main results in the RDPLF in 2020. It highlights important differences in the practices and patient profiles between French-speaking countries. Mortality in patients with clinical symptoms of COVID-19 varied from 15 to 63% depending on the country. A slight drop in the incidence rate for peritoneal dialysis in 2020 was observed when the Covid-19 pandemic should have favored a dialysis treatment at home. In patients with HHD, daily hemodialysis five days a week, at a low flow rate of dialysate, is predominant in the new centers and sometimes begins to appear as a mode of transition which allows to maintain at home patients who cannot anymore be treated by PD. In HHD, the use of a central catheter is frequent in Belgium while this is exceptional in France. Likewise, in France, puncture of an arteriovenous fistula remains classic, while in Belgium the Buttonhole technique is widely preferred. We did not observe COVID-19 mortality in HHD in 2020 but only 47% of HDD patients are included in the RDPLF while 98% of PD patients are included.